2019
DOI: 10.2507/daaam.scibook.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Study on Powder Mixed Elecrtical Discharge Machining Process: A Review

Abstract: Powder mixed electric discharge machining (PM-EDM) process is a hybrid machining process by which the required profile is attained using thermal energy of sparks between tool and workpiece with addition of powder in dielectric fluid at low pulse energy. PM-EDM process enhances the capabilities of EDM process on machining of difficult to cut materials. This chapter explores the findings of research work carried out so far in the domain of PM-EDM of different hard and conductive materials. The effect of aided co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…84,88,89 A progressive method in the flank of the augmentation of the capabilities of conventional EDM process is Powder Mixed EDM. 90,91 Padhee et al 92 presented the contrast between EDM and PMEDM while using paraffin as a dielectric. It was observed that the MRR was higher for PMEDM as compared to conventional EDM.…”
Section: Meticulous and Lucid Study Of Powder Mixed Edmmentioning
confidence: 99%
“…84,88,89 A progressive method in the flank of the augmentation of the capabilities of conventional EDM process is Powder Mixed EDM. 90,91 Padhee et al 92 presented the contrast between EDM and PMEDM while using paraffin as a dielectric. It was observed that the MRR was higher for PMEDM as compared to conventional EDM.…”
Section: Meticulous and Lucid Study Of Powder Mixed Edmmentioning
confidence: 99%